Programmed Cell Senescence in the Mouse Developing Spinal Cord and Notochord - Domínguez-Bautista, Jorge Antolio; Acevo-Rodríguez, Pilar Sarah; Castro-Obregón, Susana (Frontiers in Cell and Developmental Biology, 2021)
Programmed cell senescence is a cellular process that seems to contribute to embryo development, in addition to cell proliferation, migration, differentiation and programmed cell death, and has been observed in evolutionary distant organisms such as mammals, amphibians, birds and fish. Programmed cell senescence is a phenotype similar to stress-induced cellular senescence, characterized by the expression of the cell cycle inhibitors p21CIP1/WAF and p16INK4A, increased activity of a lysosomal enzyme with beta-galactosidase activity (coined senescence-associated beta-galactosidase) and secretion of growth factors, interleukins, chemokines, metalloproteases, etc., collectively known as a senescent-associated secretory phenotype that instructs surrounding tissue. How wide is the distribution of programmed cell senescence during mouse development and its specific mechanisms to shape the embryo are still poorly understood. Here, we investigated whether markers of programmed cell senescence are found in the developing mouse spinal cord and notochord. We found discrete areas and developmental windows with high senescence-associated beta galactosidase in both spinal cord and notochord, which was reduced in mice embryos developed ex-utero in the presence of the senolytic ABT-263. Expression of p21CIP1/WAF was documented in epithelial cells of the spinal cord and the notochord, while p16INK4A was observed in motoneurons. Treatment with the senolytic ABT-263 decreased the number of motoneurons, supporting their senescent phenotype. Our data suggest that a subpopulation of motoneurons in the developing spinal cord, as well as some notochord cells undergo programmed cell senescence.